Short-term outcomes of surgery in elderly patients with colorectal cancer - Mohamad Salmi, Muhammad Irfan; Elagili, Faisal; Md Nor, Azmi; M., Mustapha; M., Suhaimi; N., Abd Manaf; S., Parthasarathee; M., Senin (Wolters Kluwer, 2023)
Background: Surgery remains the mainstay of treatment for colorectal cancers. The implications of the use of surgery in elderly patients are not clear. Aim: To assess the effect of surgery on short-term outcomes in elderly patients with colorectal cancer. Methods: Colorectal cancer patients undergoing surgical resection from December 2017 - September 2022 were identified from charts and retrospectively examined. Patients were grouped using a cut-off of 65 years into two groups. Demographic and clinicopathological variables, surgery type, and short-term outcomes were compared between the two groups. Results: One hundred six patients were included in the study (55 age <65 and 51 age≥ 65). The two groups were similar in the patient’s characteristics. In the elderly group, the median age was 72 years,(65 to 94 years). The mean number of in-hospital days and major complication rate did not differ between groups (p=0.24; p=0.83, respectively). In elderly patients, the 30-day postoperative mortality rate was 12% as compared to 0% in younger patients (p = 0.009). On univariate analysis, the only factor associated with 30-day postoperative mortality was advanced age (p = 0.01). Limitations: This study was limited because of its retrospective nature and single center Conclusion: According to our study, colorectal cancer patients over the age of 65 who undergo surgery have considerably higher mortality rates related to their advanced age. To develop a complete CRC treatment strategy, one of the elements we must consider is aging.